Continuation of mild solution for abstract fractional integro-differential equations (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2022)
In this paper we study the existence of local, global mild solution for the abstract fractional integro-differential Cauchy problem.
Keywords: Integro-differential equations; resolvent of operators; fractional differential equation; global mild solution.